The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/jor.20641
|View full text |Cite
|
Sign up to set email alerts
|

Complex, multidimensional thumb movements generated by individual extrinsic muscles

Abstract: The objective of this study was to investigate three-dimensional thumb joint movements produced by individual extrinsic thumb muscles. Ten cadaveric arms were dissected to expose the musculotendinous junctions of the flexor pollicis longus (FPL), abductor pollicis longus (APL), extensor pollicis brevis (EPB), and extensor pollicis longus (EPL). Each muscle/tendon was loaded to 10% of its maximal force capability whereas three-dimensional angular movements of the carpometacarpal (CMC), metacarpophalangeal (MCP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…This interjoint coordination may be attributable to the extrinsic muscles and torques created by the tensioned muscles on the joints it crosses [17]. Although tasks performed in this study were different from Li’s study [17], we suspected that the negative correlation between adjacent joints was a result of interjoint coordination for the PA glide technique requirements. Due to the different levels of experience, each group likely adapted to different control patterns in order to direct force more efficiently.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This interjoint coordination may be attributable to the extrinsic muscles and torques created by the tensioned muscles on the joints it crosses [17]. Although tasks performed in this study were different from Li’s study [17], we suspected that the negative correlation between adjacent joints was a result of interjoint coordination for the PA glide technique requirements. Due to the different levels of experience, each group likely adapted to different control patterns in order to direct force more efficiently.…”
Section: Discussionmentioning
confidence: 82%
“…Novice participants appeared to respond to tip forces by controlling the IP joint without paying proper attention to the proximal joints while experienced participants controlled both the IP and CMC joints during the process of directing force to the target. Li et al [17] observed interjoint coordination, which was coordination among multiple thumb joints in a specific thumb movement direction. This interjoint coordination may be attributable to the extrinsic muscles and torques created by the tensioned muscles on the joints it crosses [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study confirmed variable pronation at the IP joint of the thumb previously demonstrated by these ex vivo studies. [1][2][3][4][5][6][7] Furthermore, we propose that, using accepted noninvasive photographic methodology, 10,11 preoperative IP joint pronation can be reliably measured and incorporated into thumb IP joint arthrodesis procedures. In cases with distorted thumb pathology, comparative measurements can be taken from the contralateral thumb IP joint.…”
Section: Table 3 Analysis Of Single Variance and Posttest Bonferronimentioning
confidence: 99%
“…5,6 Extension, valgus, and external rotation or supination is provided by the extensor expansion receiving fibers from abductor pollicis brevis, ulnar head of flexor pollicis brevis/1st palmar interosseous, and extensor pollicis longus, because the IP joint axis of rotation is not perpendicular to the proximal phalanx. 5,7 When performing a pollicization, arthrodesing or replacing the IP joint of the thumb, 8 this pronation can be lost.…”
mentioning
confidence: 99%